A history of the foundation of mathematics - Fox, Philip (My University, 1897)
Introduction: A history of mathematics is instructive to the student. It shows him the paths in which mathematicians have gone to accomplish their results; it shows him the things which have made openings for great progress, such as an invention of a good notation. In the study he sees what problems have been solved or what cannot be solved and so does not waste his time on them. He sees the mistakes of others and avoids them. The history inspires the teacher as well as the student. A teacher who can tell the history of various problems holds the interest of his class well. If he can make his pupil wonder at the deep thought placed on one problem he has done that pupil a great service. Florian Cajori says: “The history of mathematics is one of the large windows through which the philosophic eye loos into the past ages and traces the line of intellectual development.” It is plain to see that as civilization spreads and gets a firmer hold on the people the sciences deepen and so the development of mathematics is an index to the history of civilization.
Citation: Fox, Philip. A history of the foundation of mathematics. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Mathematics; History; Theses; Manuscripts (documents)